(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the problem questions related to investigation of terrorism as crimes being dangerous for environment and humanity are examined in whole. Also questions use special knowledge in DNA form examinations. At the same time in the article paid attention on questions of improvement of methods under account and analysis of DNA data given at regional level. Key words: Act of terrorism, special knowledge, examination, DNA, authentication, DNA analysis, DNA accounting.